Improvement of Physical Performance and Quality of Life After Rehabilitation Program for Total Knee Replacement in Geriatric Patient - Andi Dala Intan; Juan Suseno (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Early medical rehabilitation after Total Knee Replacement (TKR) was necessary to optimize healing process and reduce pain postoperative that can restrain patients’ activity.Case Presentation: A 66-years-old women had right TKR due to osteoarthritis genu dextra with chronic pain. Patient has muscle weakness on affected leg, and still not able to walk. Medical Rehabilitation(MR) program started one day after surgery for 4 weeks. After 4 weeks of MR program, patient had mild pain, and can walk for 100 m. Pain intensity by visual analogue scale (VAS) reduced from 7/10 to2/10, knee flexion increased from 70° to120°, right quadriceps muscle strength increased from 4 to 5 by manual muscle test (MMT), time to do physical performance by time up and go (TUG) was reduced from15 to 12.8 sc, activity daily living (ADL) by Barthel Index sco re increased from 4 to 8.Conclusion: Four weeks Rehabilitation Medicine program in geriatric patient with post Right TKR for 4 weeks, effective to improved muscle strength, balance, and ADL.Keywords: Medical rehabilitation, total knee replacement, geriatric, physical performance, quality of life